424 Improving Interprofessional Teamwork in Plastic Surgery: A Novel Approach to Microsurgical Skills Training for Theatre Nurses. (12th October 2021) - Gowda, S; Mohan, A
Abstract: Aim: Shared mental models between surgeons and scrub nurses allow them to effectively communicate with each other and react efficiently to intraoperative complications. Microsurgery poses unique challenges including the use of an operating microscope, fine instruments, and restricted views of the operative field. Our aim was to design and deliver a microsurgical skills session for theatre nurses and evaluate whether attendance influenced perceived understanding of microsurgery and ability in day-to-day role. Method: A microsurgical training day for theatre nurses was delivered. This consisted of an introduction to and positioning of the operating microscope and three practical stations involving increasingly complex motor tasks, designed to highlight the importance of instrument handling and improve awareness of microsurgical challenges. Consultant plastic surgeons acted as scrub nurses to add an element of role-reversal. Qualitative and quantitative feedback was collected. Results: Eight theatre nurses participated, all responded 'strongly agree' or 'agree' that the training was enjoyable, improved their understanding of microsurgery and was relevant and helpful to their day-to-day role. All attendees strongly agreed that they would partake in similar sessions in the future. Conclusions: Role-reversal and skills-based training is a valuable tool in improving multidisciplinary collaboration in microsurgery. Increasing shared knowledge of complex procedures prospers effective teamwork and communication, which leads to improved efficiency and better patient care. Our study is a first step towards development of a standardized microsurgical skills course for theatre nurses and has broader implications for interprofessional education across all surgical specialties.